The Use of Disability Interactive Media to Improve Beginning Reading for Children with Multiple Disabilities Class III SDLB In SLB Agrowisata Shaleha Panjalu - Abadi, Reza Febri (The Center for Disability Studies and Services Brawijaya University, 2021)
This research is based on the problem of lack of the ability to read the beginning, the ability to recognize all the letters of the alphabet has not been felt, and has not been able to incorporate letters into syllables and words in children with multiple impairments. Research aims to improve the ability to read the beginning of children with multiple impairments with target behavior, namely the ability to read syllables and word reading ability. The subject of this study was a child with a multiple impairments of class III SDLB in SLB Agrowisata Shaleha Panjalu. The method used is Single Subject Research with A-B-A research design. The processed Data is presented in a simple descriptive statistical form through graphs and percentage values. The results showed a significant increase in the ability to read the beginning of research subjects using Disability Interactive Media with the evidence that the turnover of the mean level value of the behavior of the syllable reading ability the baseline-1 (A1) phase gets an average value of 50%, the intervention phase (B) Gets an average value of 86.8% and the baseline-2 phase (A2) Gets an average value of 78.5%. Then a comparison of the mean level of the second target behavior, i.e. the ability to read word between baseline-1 (A1) Gets an average value of 33%, the intervention phase (B) Gets an average value of 81.37% and the baseline-2 phase (A2) Gets an average value of 75%.